Bacterial Diversity as a Predictor of Beef Quality and Safety - Kang, Seong-San (Curtin University, 2021)
Shiga toxin-producing Escherichia coli (STEC) is an important foodborne and regulatory pathogen in the beef industry. This study used high throughput sequencing technology to provide deeper analysis of changes in bacterial communities and subsequent effect on the presence of STEC throughout beef processing in Australian abattoirs. The 16S rRNA gene profiling demonstrated that investigating ecological shifts within bacterial communities can provide insights into controlling STEC contamination and improving efficiency of STEC detection and isolation.